Word Formation Analysis Of Slang Words Used By Podcast Kesel Aje - Azhari, Muhammad; Ardi, Havid (English Language and Literature, 2023)
This research aimed at finding the type of slang words and the type of word-formation of slang words used by Podcast Kesel Aje.  The type of this research was descriptive research. This study employed George Yule's theory of word formation processes (2010). In the finding, the researcher found 58 slang words used by Podcast Kesel Aje. The researcher found eight types of slang word-formation processes used by Podcast Kesel Aje. They were coinage, borrowing, compounding, clipping, blending, acronym, derivation, and multiple processes. The researcher found 14 slang words with compounding type (24.13%), 11 slang words with acronym type (18.96%), 10 slang words with borrowing type (17.24%), 7 slang words with multiple processes type (12.06) 5 slang words with blending type (10.34%), 5 slang words with clipping type (8.62%), 3 slang words with coinage type (5.17%), and 3 slang words with derivation type (5.17%). The most dominant types of slang word-formation used by Podcast Kesel Aje is compounding.